Sex Differences in Correlates of Intermediate Phenotypes and Prevalent Cardiovascular Disease in the General Population - Schnabel, Renate B.; Wild, Philipp S.; Prochaska, Jürgen H.; Ojeda, Francisco M.; Zeller, Tanja; Rzayeva, Nargiz; Ebrahim, Ariana; Lackner, Karl J.; Beutel, Manfred E.; Pfeiffer, Norbert; Sinning, Christoph R.; Oertelt-Prigione, Sabine; et al. (Frontiers in Cardiovascular Medicine, 2015)
Background-There are marked sex differences in cardiovascular disease [CVD] manifestation. It is largely unknown how the distribution of CVD risk factors or intermediate phenotypes explain sex-specific differences. Methods and Results-In 5000 individuals of the population-based Gutenberg Health Study, mean age 55±11 years, 51% males, we examined sex-specific associations of classical CVD risk factors with intima-media thickness, ankle-brachial index, flow-mediated dilation, peripheral arterial tonometry, echocardiographic and electrocardiographic variables. Intermediate cardiovascular phenotypes were related to prevalent CVD (coronary artery disease, heart failure, stroke, myocardial infarction, lower extremity artery disease [LEAD] N=561). We observed differential distributions of CVD risk factors with a higher risk factor burden in men. Manifest coronary artery disease, stroke, myocardial infarction and LEAD were more frequent in men; the proportion of heart failure was higher in women. Intermediate phenotypes showed clear sex differences with more beneficial values in women. Fairly linear changes towards less beneficial values with age were observed in both sexes. In multivariable-adjusted regression analyses age, systolic blood pressure and body mass index were consistently associated with intermediate phenotypes in both sexes with different ranking according to random forests, maximum model R² 0.43. Risk factor-adjusted associations with prevalent CVD showed some differences by sex. No interactions by menopausal status were observed. Conclusions-In a population-based cohort we observed sex differences in risk factors and a broad range of intermediate phenotypes of noninvasive cardiovascular structure and function. Their relation to prevalent CVD differed markedly. Our results indicate the need of future investigations to understand sex differences in CVD manifestation.